Dando: La definición de derivadas; La definición de e. Resuelva:
ln(x) = lim(d->0) [ ln(x+d) - ln(x) ] / d = lim ln((x+d)/x) / d = lim (1/d) ln(1 + d/x) = lim [ ln (1 + d/x)(1/d) ]. Fije u=d/x y substitua: lim(u->0) [ ln (1 + u)(1/(ux)) ] = 1/x ln [ lim(u->0) (1 + u)(1/u) ] = 1/x ln (e) (La definición de e) = 1/x.
Fije u=d/x y substitua:
lim(u->0) [ ln (1 + u)(1/(ux)) ] = 1/x ln [ lim(u->0) (1 + u)(1/u) ] = 1/x ln (e) (La definición de e) = 1/x.
Contact us | Advertising & Sponsorship | Partnership | Link to us © 2000-2023 Math.com. All rights reserved. Legal Notices. Please read our Privacy Policy.